Mouse phenotypes : a handbook of mutation analysis - Papaioannou, Virginia E; Behringer, Richard (Cold Spring Harbor Laboratory Press, 2005)
The generation of mutant mice raises many questions about the best means of phenotypic analysis, breeding, and maintenance. The answers are now available from two experts with a wealth of detailed knowledge never previously assembled in one volume. Informal and highly practical, this handbook provides stepÂ–byÂ–step methods for troubleshooting experiments, from the basics of gene targeting through the analysis of postnatal effects.
Keywords: mutace; biologie; veterinární lékařství; Phenotype; fenotyp; Mice; Mutation; myši